The age of innocence : nuclear physics between the first and second world wars - Stuewer, Roger H. (Oxford University Press, 2018)
This history of nuclear physics sets the experimental innovations and theoretical breakthroughs in the field in the period between the two world wars within the contexts of the lives and personalities of the physicists who made them and the physical, intellectual, and political environments of the countries and institutions in which they worked.